2009
DOI: 10.1111/j.1600-0501.2009.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in graft height after maxillary sinus floor elevation with different grafting materials: radiographic evaluation with a minimum follow‐up of 4.5 years

Abstract: Both beta-TCP and mandibular bone grafts resulted in radiographic reduction of the vertical height over the 5-year period following maxillary sinus floor elevation. After an initial height reduction in the first 1.5 year, subsequent changes were minimal. No significant differences were observed between the two types of grafting material. There was no statistically significant difference in reduction between the three locations for vertical bone height and graft height, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
94
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 17 publications
(25 reference statements)
11
94
1
4
Order By: Relevance
“…The clinical use of β-TCP particulate bone grafting materials in implant dentistry as well as oral and maxillofacial surgery has been well documented by numerous clinical studies which demonstrated excellent success rates [2,6,[8][9][10][11][12]. As a result, tricalcium phosphate is currently regarded as a bone grafting material well suited for various clinical applications such as sinus floor augmentation procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical use of β-TCP particulate bone grafting materials in implant dentistry as well as oral and maxillofacial surgery has been well documented by numerous clinical studies which demonstrated excellent success rates [2,6,[8][9][10][11][12]. As a result, tricalcium phosphate is currently regarded as a bone grafting material well suited for various clinical applications such as sinus floor augmentation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The use of autogenous bone is still considered the gold standard for SFA due to its excellent osteogenic potential [9,12,31,32]. Hence, in the present study 10% (vol%) autogenous bone chips were added to the grafting materials in order to ensure a sufficient supply with osteogenic cells such as osteoblasts and osteoprogenitor cells, which support new bone formation and graft consolidation in combination with the osteoprogenitor cells which migrate from the sinus floor into the grafted area [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-TCP is also known to be a suitable bone substitute that will biodegrade and can be replaced by newly mineralising bone tissue without fibrous tissue proliferation 3) . In recent years, the use of β-TCP as an alloplastic bone graft material for sinus grafting procedures has also received increasing attention in oral implant therapy 4,5) . β-TCP particles in the extraction socket are clinically osteoconductive 6).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is preferred as bone graft material for the maxillary sinus due to the low risk of edema and nerve injury compared to mental bone. Bone in the maxillary tuberosity area is mostly composed of trabecular bone and used limitedly due to the lack of bone mass but preferred as maxillary sinus bone graft material due to the ease of harvesting and absence of specific complications except the risk of perforation 8) . To remedy such short comings, the use of bone graft material by non-autogenous bone was discussed.…”
Section: Introductionmentioning
confidence: 99%